PRE-SERVICE TEACHERS’ PERCEPTIONS OF THE CHALLENGES IN TEACHING ENGLISH TO YOUNG LEARNERS - Iwan Dudy Gunawan (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
This study aims to investigate the perceptions of pre-service teachers regarding the challenges encountered while teaching English to young learners. It also assesses the effectiveness of a TEYL course in mitigating these challenges. A descriptive quantitative research design was employed, collecting data from 15 undergraduate students participating in the TEYL course at Pasundan University, Indonesia. Data collection involved a questionnaire comprising Likert-scale items and open-ended questions, enabling analysis of both quantitative and qualitative insight. Research findings indicate that the primary challenges faced by students were classroom management, sustaining children's focus, and developing suitable and stimulating materials. However, the TEYL course was perceived as highly beneficial, offering valuable support through the introduction of child-centered methodologies, including storytelling, songs, and visual aids. A significant majority (over 80%) of participants reported that the course enhanced their understanding of young learners and strengthened their confidence in teaching. Significant demand was voiced by the students for enhancing practical teaching opportunities, who also underscored the relevance of incorporating technology and real-world exposure into their learning experiences. This study suggests that future TEYL programs should prioritize practicum-centered instruction and technological integration to connect theoretical knowledge to real-world classroom scenarios effectively.